Ciphertext-only fault analysis of the SIMON lightweight cipher - Wei LI; Yixin WU; Dawu GU; Jiayao LI; Shan CAO; Menglin WANG; Tianpei CAI; Xiangwu DING; Zhiqiang LIU (Tongxin xuebao)
The ciphertext-only fault analysis on the SIMON cipher was proposed by injecting a random nibble fault under the random nibble fault model.After injecting faults,every faulty ciphertext could be decrypted and the statistical distribution of all intermediate states were analyzed by the attackers.On the basis of the previous distinguishers of SEI,GF,MLE,MLE-SEI,GF-SEI and GF-MLE,four novel distinguishers of GF-MAP,HW-MLE,GF-HW and HW-MAP were proposed to reduce faults.The results show that the SIMON cipher cannot resist against the ciphertext-only fault analysis.It provides an important reference for security analysis of other ciphers.